2020
DOI: 10.3390/brainsci10120965
|View full text |Cite
|
Sign up to set email alerts
|

EEG-Based BCI System to Detect Fingers Movements

Abstract: The advancement of assistive technologies toward the restoration of the mobility of paralyzed and/or amputated limbs will go a long way. Herein, we propose a system that adopts the brain-computer interface technology to control prosthetic fingers with the use of brain signals. To predict the movements of each finger, complex electroencephalogram (EEG) signal processing algorithms should be applied to remove the outliers, extract features, and be able to handle separately the five human fingers. The proposed me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…However, CSP does not always perform perfectly with the SVM algorithm. Earlier studies [ 172 , 175 , 258 ] have compared the performance of ANNs and LDA with SVM. Jia et al [ 175 ] have compared the results obtained by using backpropagation neural network (BPNN) and SVM algorithms and found that BPNN with CSP consistently outperformed SVM.…”
Section: Discussionmentioning
confidence: 99%
“…However, CSP does not always perform perfectly with the SVM algorithm. Earlier studies [ 172 , 175 , 258 ] have compared the performance of ANNs and LDA with SVM. Jia et al [ 175 ] have compared the results obtained by using backpropagation neural network (BPNN) and SVM algorithms and found that BPNN with CSP consistently outperformed SVM.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, they reflect the function of some organs (e.g., brain, muscles, eyes) in the form of electrical activity, providing relevant information about them [44,45]. For this reason, biopotentials are used as control signals in many biomedical HMI applications [25,42,[46][47][48][49][50][51][52][53][54][55][56][57][58][59]. These biosignals have their origin in electrophysiological phenomena associated with biochemical events occurring at a cellular level.…”
Section: Hmi Control Based On Biopotentialsmentioning
confidence: 99%
“…Clear examples are subjects affected by neuromuscular disorders, such as MD, ALS, MS, SCI, and CP, or even poststroke patients and amputees [5,[18][19][20]. In this scenario, two main targets can be identified: robotic control [14,15,34,49,50,[64][65][66][67][68][69] and prosthetic control [46][47][48][69][70][71][72][73][74][75][76][77][78].…”
Section: Eeg-based Hmismentioning
confidence: 99%
See 2 more Smart Citations